Study of Railway Wheel Service Period Prediction at Maximum Curved Distance Based on Flange Wear Level - Perwira, Dimas Adi; Marsusiadi, Edi Nyoto Setyo; Nurhadi, Muhamad; Atmaja, Dadang Sanjaya; Ricardo, Daffa Ricta (Universitas Pahlawan Tuanku Tambusai, 2024)
The study aimed to comprehensively analyze the impact of curves on railway tracks on the wear level of train wheel flanges. The case study focused on the Yogyakarta-Kutoarjo line, which presented a unique track with several curves. Data collection involved meticulous measurements of wheel flange wear on regularly operating trains along the line, along with a thorough analysis of track geometry, train operating speeds, and wheel materials. This quantitative research employed the linear regression method to analyze the data. The findings revealed a notable correlation between wheel flanges A and B's wear levels and curves on the Yogyakarta-Kutoarjo railway line, with 1.036 mm and 1.495 mm of wear on wheels A and B, respectively. The R2 value falling within the range of 0.7521 to 0.9678 indicated a significant influence on wheel flange wear. The study also identified the furthest curved distances, 102,304.80 km for wheel A and 136,857.00 km for wheel B. This research is anticipated to make meaningful contributions to the advancement of railway track and wheel maintenance, ultimately enhancing railway systems' safety and operational efficiency.